The On/Off Ph-Dependent Electrocatalytic Activity of the Perfluorinated Iron Phthalocyanine for the Oxygen Reduction Reaction and Electrochemical Hardness as a Reactivity Descriptor: Experimental and Theoretical Study - Zagal-Moya, J; Zagal-Moya, J; Melo-Hurtado, F; Cardenas-Jiron, G; Bernal-Valenzuela, R; Ponce-Hormazabal, I; Imbarack-Candia, E; Imbarack-Candia, E; Venegas-Toledo, R; Onate, R (American Chemical Society, 2025)
Perfluorinated iron phthalocyanine 16(F)FePc is probably the most active MN4 molecular catalyst reported to promote the oxygen reduction reaction (ORR) in alkaline media. Its high activity is attributed to the electron-withdrawing properties of the fluoro substituents, which promote a hard-iron active site to interact with a hard-O2 molecule. However, its activity has been explored shallowly. Here, we modified an edge plane-pyrolytic graphite surface (EPG) with 16(F)FePc to promote ORR in different pH media to build a Pourbaix diagram as an electrocatalytic roadmap for 16(F)FePc. Furthermore, the recently proposed reactivity descriptor for ORR, known as the “electrochemical hardness” (ΔEh), was determined in the EPG/16(F)FePc system at different pH. It was found that the catalyst’s reactivity is inversely proportional to the ΔEh values, so small values conduct to high activity. The same behavior was obtained for the oxidation-reduction hardness (ηox-red) parameter, which was theoretically determined in this work by DFT calculations. The theoretical ηox-red suggests a decrease of the Fe(II) reactivity with the increase of nitrogen atom protonation in the 16(F)FePc, supporting the pH-dependent ΔEh values. Moreover, a pH-dependent locked/unlocked mechanical switch behavior for the 16(F)FePc was determined, attributed to the iron center motion above the N4-plane without a demetalation process. We observed this phenomenon in an acid media using electrochemical techniques coupled with Surface-Enhanced Raman Spectroscopy (EC-SERS), monitoring the Fe(II)/(I), Fe(III)/(II) redox potentials, and the in situ ORR process. The scanning tunneling microscopy-based break junction technique (STM-BJ) revealed this mechanical switch at the single-molecule level. Conversely, the mechanical switch is locked in alkaline media, and the 16(F)FePc is in an on-catalytic state for ORR. Therefore, the unlocked mechanical switch could explain the low ORR catalytic activity of the 16(F)FePc in acidic media (off-catalytic state). These findings are crucial for understanding the catalytic behavior of 16(F)FePc, especially in acid media. © 2024 American Chemical Society.